2002
DOI: 10.1381/096089202321019602
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Roux-en-Y Gastric Bypass – Evaluation of Three Different Techniques

Abstract: Whichever technique is used to construct the gastrojejunostomy, LRYGBP is a safe, effective and technically feasible operation for morbidly obese patients. We recommend the technique of constructing the gastrojejunostomy with an endocutter cartridge and closing the anastomotic incision with an endo TA stapler, as it saved time and reduced the incidence of the essential complications in gastric bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 11 publications
1
39
2
1
Order By: Relevance
“…4 Another well-known advantage of laparoscopic GBP is the reduction in wound-related complications because of the smaller access incision. [4][5][6][7][8] The advantages of laparoscopic GBP, however, come with a possible change in the type and frequency of postoperative complications. The technique of laparoscopic GBP has evolved since its inception, and this learning process can be associated with adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another well-known advantage of laparoscopic GBP is the reduction in wound-related complications because of the smaller access incision. [4][5][6][7][8] The advantages of laparoscopic GBP, however, come with a possible change in the type and frequency of postoperative complications. The technique of laparoscopic GBP has evolved since its inception, and this learning process can be associated with adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds well to RCT data in gastric cancer patients (EL 1b [142,300,307,353]). In obese patients there is only a trial with pseudorandomization by alternation (EL 2b [1]), where stenosis occurred in 10 of 30 handsewn anastomoses and 8 of 60 mechanical anastomoses (p = 0.047 by Fisher's exact test). Laterolateral anastomoses are currently standard and can be created by circular or linear stapling, although the latter seems perferable.…”
Section: Rygbmentioning
confidence: 99%
“…The use of a circular stapler allows the size of the gastric outlet to be controlled precisely. Although Wittgrove and Clark [7] did not report complications with the transoral technique, other investigators have documented complications such as injury to the esophagus [1]. Scott et al [5] also reported a case of esophageal injury that occurred during transoral placement of the anvil.…”
Section: Discussionmentioning
confidence: 99%